A survey on pesticide use and self-reported respiratory health symptoms among paddy farmers in Tanjung Karang, Malaysia - Hamsan, Hazwanee; Ho, Yu Bin; How, Vivien; Hashim, Zailina; Saari, Nazamid (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Tanjung Karang is a paddy growing town in Selangor, Malaysia. The paddy farmers in Tanjung Karang were using pesticides to control pests from invading the crops during agricultural activities with limited knowledge of its deleterious effects on their health. Objective: This study aims to (i) determine the respiratory health symptoms of paddy farmers due to occupational exposure of commonly used pesticides through inhalation and (ii) assess correlations between climatological conditions and the concentrations of pesticides in personal air samples among paddy farmers in Tanjung Karang, Malaysia. Methods: A cross-sectional study was carried out to assess the occupational exposures to pesticides among 83 paddy farmers in Kampung Sawah Sempadan. The data were collected with face-to-face interviews with the farmers based on a set of questionnaire. Results: The self-reported respiratory health symptoms of paddy farmers were as follows: breathing difficulty (16.9%), chest pain (15.7%), cough (41.0%), phlegm (39.8%), and wheezing (18.1%). Simple logistic regressions analysis indicated that exposure to azoxystrobin, buprofezin, chlorantraniliprole, fipronil, isoprothiolane, pretilachlor, propiconazole, tricyclazole and trifloxystrobin were contributing factors that affect self-reported respiratory health symptoms in this study. Spearman’s correlation coefficient test stated that the concentrations of chlorantraniliprole, fipronil and pymetrozine were affected by wind speed and temperature. Conclusion: The information obtained in this study is useful to understand the exposure of pesticides among paddy farmers and useful for risk management in the agricultural community.